Functional Assessment of Cerebral Artery Stenosis by Angiography-Based Quantitative Flow Ratio: A Pilot Study - Huang, Kangmo; Yao, Weihe; Du, Juan; Wang, Fang; Han, Yunfei; Chang, Yunxiao; Liu, Rui; Ye, Ruidong; Zhu, Wusheng; Tu, Shengxian; Liu, Xinfeng (Frontiers in Aging Neuroscience, 2022)
Background Increasing attention has been paid to the hemodynamic evaluation of cerebral arterial stenosis. We aimed to demonstrate the performance of angiography-based quantitative flow ratio (QFR) to assess hemodynamic alterations caused by luminal stenoses, using invasive fractional pressure ratios (FPR) as a reference standard. Methods Between March 2013 and December 2019, 29 patients undergoing pressure gradient measurement of cerebral atherosclerosis were retrospectively enrolled. Wire-based FPR was defined by the arterial pressure distal to the stenotic lesion (Pd) to proximal (Pa) pressure ratios (Pd/Pa). FPR<0.70 or FPR<0.75 was assumed as hemodynamically significant stenosis. The new method of computing QFR from a single angiographic view, i.e., the Murray law-based QFR, was applied to the interrogated vessel. An artificial intelligence algorithm was developed to realize the automatic delineation of vascular contour. Results FPR and QFR were assessed in 38 vessels from 29 patients. Excellent correlation and agreement were observed between QFR and FPR (r=0.879, P<0.001; mean difference [bias]: -0.006, 95% limits of agreement: -0.198 to 0.209, respectively). Intra-observer and inter-observer reliability in QFR were excellent (intraclass correlation coefficients, 0.996 and 0.973, respectively). For predicting FPR<0.70, the area under the receiver-operating characteristic curves (AUC) of QFR was 0.946 (95%CI, 0.820 to 0.993). The sensitivity and specificity of QFR<0.70 for identifying FPR <0.70 was 88.9% (95%CI, 65.3% to 98.6%) and 85.0% (95%CI, 62.1% to 96.8%). For predicting FPR<0.75, QFR showed similar performance with an AUC equal to 0.926. Conclusion Computational QFR from a single angiographic view achieved comparable results to the wire-based FPR. The excellent diagnostic performance and repeatability empower QFR with high feasibility in the functional assessment of cerebral arterial stenosis.